ASSESSING THE INFLUENCE OF FAIR VALUE ACCOUNTING ON THE PERFORMANCE OF CONSUMER GOODS COMPANIES IN CROSS RIVER STATE, NIGERIA (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
This study investigates the influence of fair value accounting (FVA) on the financial performance of consumer goods companies in Cross River State, Nigeria. Utilizing primary data collected through structured questionnaires from 120 respondents, including accountants, financial managers, and auditors from selected firms, the research examines how FVA impacts key performance indicators such as profitability, return on assets (ROA), and firm value. The study adopts a survey research design and employs regression analysis to test hypotheses. Findings reveal that FVA significantly affects profitability and ROA, having minimal influence on firm value. The results suggest that while FVA enhances transparency and relevance in financial reporting, its application in an emerging market like Nigeria faces challenges like market illiquidity and valuation complexities. The study recommends that consumer goods companies in Cross River State adopt hybrid valuation models and invest in capacity building to improve FVA implementation. These findings contribute to the ongoing discourse on adopting International Financial Reporting Standards (IFRS) in developing economies.